2016
DOI: 10.1016/j.partic.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of restitution for particles impacting on wet surfaces: An improved experimental approach

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 12 publications
7
43
0
Order By: Relevance
“…Briefly, the elastohydrodynamic theory neglects the effects of layer thickness in the energy dissipation, manifesting as the absence of layer thickness in the definition of St d . However, it has been proved that the layer thickness plays an important role in the impact (Antonyuk et al, 2009;Crüger et al, 2015;Ma et al, 2015). Therefore, in our early work (Ma et al, 2013), we proposed a modified Stokes number, St m to incorporate the effects of layer thickness:…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the elastohydrodynamic theory neglects the effects of layer thickness in the energy dissipation, manifesting as the absence of layer thickness in the definition of St d . However, it has been proved that the layer thickness plays an important role in the impact (Antonyuk et al, 2009;Crüger et al, 2015;Ma et al, 2015). Therefore, in our early work (Ma et al, 2013), we proposed a modified Stokes number, St m to incorporate the effects of layer thickness:…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we will present the results for normal impacts of a glass sphere on a flat glass plate covered by a layer of water, from our VOF‐IBM simulations as well as from a series of experiments performed by Crüger et al The influence of impact velocity, liquid layer thickness, liquid viscosity, particle size, and surface tension on the wet restitution coefficient will be included. Some of the experimental data, which are presented in this article, can also be found in Crüger et al Unless otherwise mentioned, the parameters listed in Table are used for the simulations. The computational domain size and the time step are varied with different combinations of the layer thickness, the impact velocity and the grid size.…”
Section: Resultsmentioning
confidence: 99%
“…As then, with the aid of an impact setup, numerous experimental investigations have been performed to study the relation of the wet restitution coefficient with the relevant parameters during normal as well as oblique collisions. Regarding the importance of liquid layer thickness, it was found that the e wet in the normal direction decreases significantly with increasing layer thickness . Conversely, increasing layer thickness has no further effect on the e wet in the tangential direction rather than causing less friction .…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the reaction rate of this is taken to be proportional to the numbers of particle per unit volume of the colliding particles. 1 Nonlinear breakage has significant impact in many engineering processes such as fluidized beds, [2][3][4][5] the bulk distribution of raindrops, [6][7][8][9] comminution systems, [10][11][12][13] and several types of milling process. [14][15][16][17] Binary collisional breakage is the specific case of the nonlinear breakage, one where the breaking behavior is influenced through the sole of collisions between two particles.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation (7)(8) is based on the Leibnitz integration rule and the mass conservation property (4). It is pertinent to mention that literature reveals most theoretical research works have comprised only with linear breakage [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and only few investigations have been presented to nonlinear breakage due to interactions between fragments, such as collision-induced fragmentation.…”
Section: Introductionmentioning
confidence: 99%